PROTOTYPE DESIGN OF LYMPHOCYTE TCD4+ RESISTANT AGAINST HIV INFECTION GENERATED FROM PERIPHERAL BLOOD HAEMATOPOIETIC STEM CELL (PBMCs) By DELETION OF 32 bp CCR5 ENCODING GENE - Purwati, Purwati (Journal of Stem Cell Research and Tissue Engineering, 2017)
AIDS epidemic has spread to all parts of Indonesia and currently more than 150 countries reported the existence of HIV/AIDS from around the world. Additionally, HIV/AIDS treatment using ARV drugs also find obstacles that must be faced in terms of host, environment and the agent. The objective of this study was to generate lymphocytes TCD4+ that are resistant to HIV infection generate from PBMCs through by deletion of 32 bp CCR5 encoding gene. In principle, this study was done in three steps. First, isolation, culture and purification of lymphocyte TCD4+ from PBMC (Mather, 2008; Rantam, et.al., 2009). Second, lymphocyte TCD4+ characterization by PCR with primer F 5'CAAGTCGAGCGCCCCGCAAGGGG-3, R 5'GTCCGAGTGTGGCTGATCATCC-3 (Thomsen, et.al., 2002; Yuwono, 2006; Hall and Ziedonis 2007; Purwati, et.al., 2009). Third, designing of lymphocyte TCD4+ prototype which was resistant to HIV infection by deletion of 32 bp CCR5 full gene. Results: Twenty-four hours after culture, there were abundant cell growths. TCD4+ lymphocytes from isolated and cultured 10 ml PBMC were found to be 2 x 107. Phenotype characterization of TCD4+ lymphocyte provided positive results, while the genotype showed similarities to that in corresponding gene bank of CCR5 variant A and variant B. Prototype of HIV resistant TCD4+ lymphocytes was made by nucleotide deletions in conserved areas, at position 554-576 bp, using restriction enzymes EcoRI checked using PCR and sequencing. In conclusion, prototype design of HIV resitent TCD4+ lymphocytes is obtained through the deletion of 32 bp CCR5 encoding full gene at GTCAGTATCAATTCTGGAA GAATTT CCAGACA using EcoRI enzyme.Keywords: HIV/AIDS, resistant TCD4+ lymphocytes, mutant 32 bp CCR5, PBMCs, deletion